Method for producing carboxyalkylated polysaccharides and method for producing biodegradable highly water-absorbent resins using the same
By employing water as the solvent and inducing high torque and temperature during the gelatinization of polysaccharides, the method effectively addresses the inefficiencies of conventional carboxyalkylation processes, enabling the production of biodegradable, hyperwater-absorbent resins with enhanced water retention properties.
Patent Information
- Application Number
- JP2024559061
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-12-22
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-12-22
AI Technical Summary
Conventional methods for producing carboxyalkylated polysaccharides are economically inefficient and difficult to scale up due to the use of alcohol-based organic solvents, which also pose environmental concerns.
A method involving the use of water as the sole solvent, with a specific water content relative to polysaccharides, and conducting the carboxyalkylation reaction under high torque and temperature induced by gelatinization, to produce carboxyalkylated polysaccharides with high substitution efficiency.
This method enhances the substitution efficiency of carboxyalkyl groups, reduces environmental impact, and facilitates mass production of biodegradable, hyperwater-absorbent resins with improved water retention ability.
Smart Images

Figure 2025512943000001_ABST
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0183169 dated December 23, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a method for producing a carboxyalkylated polysaccharide, and a method for producing a biodegradable highly water-absorbent resin using the same. [Background technology]
[0003] Recently, as interest in biomass materials has increased due to environmental issues, interest in compounds such as polysaccharides, polyaspartic acid, polyglutamic acid, etc., which are biodegradable materials, has been growing.
[0004] In particular, polysaccharides, or polysaccharides, are widely present in nature as components of plants and animals, and are attracting attention as important biodegradable materials because they are economical and easy to obtain. However, in order to be used in various industrial fields, it is necessary to replace the hydroxyl groups (-OH) present in polysaccharides with other functional groups, and methods for producing modified polysaccharides substituted with various substituents have been investigated.
[0005] Among such modified polysaccharides, carboxyalkylated polysaccharides in which a carboxyl group is introduced to the terminal group can be used in various applications requiring the inclusion of an acidic group. In particular, carboxyalkylated polysaccharides can be used as a main raw material for biodegradable superabsorbent polymers. The superabsorbent polymers (SAPs) are synthetic polymers capable of absorbing 500 to 1,000 times their weight in water, and are widely used in a wide range of applications, from sanitary products such as baby diapers to soil water retention agents for gardening, water-stopping materials for civil engineering and construction, seedling sheets, freshness-preserving agents in the food distribution field, and materials for poultices, as well as in the field of electrical insulation. Therefore, there is a need to study a method for manufacturing carboxyalkylated polysaccharides in a manner that allows industrial mass production without causing environmental problems.
[0006] However, conventional carboxyalkylation of polysaccharides has problems such as the economical efficiency being reduced by the alcohol-based organic solvent used in the carboxyalkylation reaction, and the difficulty of mass production due to process problems. Furthermore, when a large amount of the alcohol-based organic solvent is used, expensive solvent recovery equipment is required to recover and reuse the solvent after the reaction.
[0007] Thus, there remains a demand for a method for economically producing carboxyalkylated polysaccharides in large quantities for the production of biodegradable superabsorbent polymers. As a result of extensive research into such a method, it was found that such a demand can be met by using a specific content of water as the sole solvent and carrying out the carboxyalkylation reaction of polysaccharides under high torque and temperature induced by gelatinization, and thus the present invention was completed. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention relates to a method for producing a carboxyalkylated polysaccharide and a method for producing a biodegradable superabsorbent resin using the same. More specifically, the present invention relates to a method for producing a carboxyalkylated polysaccharide that exhibits high substitution efficiency by carrying out a carboxyalkylation reaction using a specific content of water under high torque induced by gelatinization, and a method for producing a biodegradable superabsorbent resin that can produce a superabsorbent resin with high water retention capacity by self-crosslinking the carboxyalkylated polysaccharide produced by such a production method. [Means for solving the problem]
[0009] In order to solve the above problems, the present invention provides a method for producing a carboxyalkylated polysaccharide, comprising the steps of: mixing a polysaccharide, a hydroxide, a metal salt of a haloalkyl carboxylic acid, and water in a reactor to carry out gelatinization and carboxyalkylation of the polysaccharide; the water is used in an amount of 0.35 to 1.0 times the weight of the polysaccharide; and the torque in the reactor is maintained at 7 to 18 Nm after gelatinization of the polysaccharide.
[0010] The present invention also provides a method for producing a biodegradable highly water-absorbent resin, comprising the steps of:
[0011] Step 1: dissolving the carboxyalkylated polysaccharide produced by the above-mentioned production method in 5 to 15 times as much water as the weight of the carboxyalkylated polysaccharide; The product of step 1 is then subjected to self-crosslinking under a pH condition of 6 to 8 while being dried (step 2). Effect of the Invention
[0012] The above-mentioned method for producing carboxyalkylated polysaccharides has an advantage that only a small amount of water is used as a solvent during the carboxyalkylation reaction, and the substitution efficiency of the carboxyalkyl group can be increased. Furthermore, since the above-mentioned method does not use an alcohol-based organic solvent as a reaction solvent, it is environmentally friendly and economical, and is suitable for mass production of carboxyalkylated polysaccharides.
[0013] Furthermore, when the carboxyalkylated polysaccharide produced by the above-mentioned production method is self-crosslinked, it is possible to produce a biodegradable highly water-absorbent resin having a high water retention capacity. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 shows the internal torque and temperature in the reactor of Example 1-2. [Diagram 2] FIG. 2 shows the internal torque and temperature in the reactor of Comparative Examples 1-3. [Diagram 3] FIG. 3 shows the internal torque and temperature in the reactor of Reference Example 1-1. [Figure 4] FIG. 4 shows the internal torque and temperature in the reactor of Reference Example 1-2. [Diagram 5] FIG. 5 shows the internal torque and temperature in the reactor of Reference Examples 1-3. [Figure 6] FIG. 6 shows the 1H NMR spectrum of the carboxymethylated starch prepared in Example 1-1. [Figure 7] FIG. 7 shows the 1H NMR spectrum of the carboxymethylated starch prepared in Example 1-2. [Figure 8] FIG. 8 shows the 1H NMR spectrum of the carboxymethylated starch produced in Reference Example 1-1. [Figure 9] FIG. 9 shows the 1H NMR spectrum of the carboxymethylated starch produced in Reference Example 1-2. [Figure 10]FIG. 10 shows the 1H NMR spectrum of the carboxymethylated starch produced in Reference Examples 1-3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "comprise", "have" and the like are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood not to preclude the presence or additional possibility of one or more other features, steps, components, or combinations thereof.
[0016] In addition, in the present invention, when a layer or element is referred to as being formed "on" or "on" another layer or element, it means that the layer or element is formed directly on the layer or element, or that other layers or elements may be additionally formed between the layers, on the object, or on the substrate.
[0017] Since the present invention can be modified in various ways and can have various forms, specific embodiments are illustrated and described in detail below, but it is not intended to limit the present invention to the specific disclosed forms, and it should be understood that the present invention includes any modifications, equivalents, or alternatives falling within the spirit and technical scope of the present invention.
[0018] Furthermore, the terminology used in this specification is merely for the purpose of referring to particular embodiments and is not intended to limit the present invention. Additionally, the singular forms used herein include the plural forms unless the context clearly indicates otherwise.
[0019] On the other hand, conventionally used superabsorbent resins are produced by polymerizing an acrylic acid monomer together with a crosslinking agent in the presence of a polymerization initiator. However, the superabsorbent resins produced in this manner are not biodegradable, causing environmental problems.
[0020] Therefore, development of superabsorbent polymers that can exhibit biodegradability has been underway. Examples of biodegradable materials from which such biodegradable polymers can be manufactured include polysaccharides, polyaspartic acids, polyglutamic acids, etc. However, it has been difficult to replace superabsorbent polymers manufactured from acrylic acid monomers because they reduce the absorption capacity, which is an important physical property of superabsorbent polymers, and are not easy to mass-produce.
[0021] For this reason, modified polysaccharides have been used in which various functional groups have been introduced into polysaccharides such as starch, which are biodegradable and readily available. However, the organic solvents used in the production of such modified polysaccharides make them unfriendly to the environment and less economical.
[0022] Therefore, the present inventors have confirmed that when gelatinizing a polysaccharide such as starch with a small amount of water while stirring, a torque is induced within the polysaccharide, and that when a carboxyalkylation reaction is carried out under a torque above a certain level, the reaction can be carried out in a short time without the need for an additional alcohol-based solvent, and the reaction efficiency (RE) can be increased compared to the case where an additional alcohol-based solvent is used, and thus completed the present invention.
[0023] The present inventors have also confirmed that when the carboxyalkylated polysaccharides prepared as described above are self-crosslinked under specific pH conditions without using an internal crosslinking agent, a biodegradable highly absorbent resin exhibiting high absorption performance can be produced. Each invention will be described in detail below.
[0024] Each invention will be described in detail below.
[0025] (Method of producing carboxyalkylated polysaccharides) A method for preparing a carboxyalkylated polysaccharide having improved reaction efficiency (RE) includes the steps of mixing a polysaccharide, a hydroxide, a metal salt of a haloalkyl carboxylic acid, and water in a reactor to gelatinize and carboxyalkylate the polysaccharide, wherein the water is used in an amount of 0.35 to 1.0 times the weight of the polysaccharide, and the torque in the reactor is maintained at 7 to 18 Nm after gelatinization of the polysaccharide.
[0026] More specifically, in the above step, the polysaccharide is first gelatinized by mixing the polysaccharide with hydroxide and water, and then the gelatinized polysaccharide is carboxyalkylated with a metal salt of a haloalkyl carboxylic acid.
[0027] At this time, the time when the gelatinization of the polysaccharide is completed can be confirmed when the torque stabilizes by measuring the internal torque in the reactor from the start of mixing to the end of mixing through a torque measuring sensor installed in the reactor. More specifically, when the polysaccharide is gelatinized by water and hydroxide, the internal heat energy increases due to the load induced during the gelatinization process, and the torque and temperature increase, and then the torque and temperature in the reactor are maintained constant when the gelatinization is completed. Therefore, the carboxyalkylation reaction of the polysaccharide may be performed under constant torque conditions in the reactor, thereby making it possible to produce a carboxyalkylated polysaccharide having a uniform degree of substitution and improved substitution efficiency.
[0028] Therefore, if the torque in the reactor after gelatinization of the polysaccharide is less than 7 Nm, there is a problem that the substitution efficiency of the carboxyalkyl group decreases, and if the torque exceeds 18 Nm, the internal temperature increases excessively, causing the water used as a solvent to evaporate, which may reduce workability, which is undesirable.
[0029] More specifically, the torque (Nm) in the step may be 7 or more, 7.5 or more, or 8 or more, and 18 or less, 16 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, or 9 or less.
[0030] The polysaccharide means a polymeric carbohydrate molecule composed of a glucose unit, including a polymeric molecule composed of a glucosamine unit in which an amino group has been introduced to the hydroxyl group bonded to the second carbon atom of the glucose unit and / or an N-acetylglucosamine unit in which an N-acetylamino group has been introduced to the hydroxyl group bonded to the second carbon atom of the glucose unit. Such polysaccharides can be classified into storage polysaccharides used as a general energy source, structural polysaccharides that form structural components of animals and plants such as the cell walls of plants and the exoskeletons of arthropods, and capsular polysaccharides that form bacterial capsules. Examples of the storage polysaccharides include starch, dextrin, glycogen, inulin, etc., examples of the structural polysaccharides include cellulose, chitin, chitosan, pectin, arabinoxylan, carrageenan, agar, etc., and examples of the capsular polysaccharides include alginate, xanthan gum, guar gum, gellan gum, dextran, welan gum, etc. Among these, those that can be gelatinized are suitable for the method of producing the carboxyalkylated polysaccharides. More specifically, the polysaccharide may be starch, dextrin, glycogen, inulin, cellulose, chitosan, pectin, agar, carrageenan, alginate, xanthan gum, guar gum, gellan gum, or a combination thereof.
[0031] Here, gelatinization of polysaccharides refers to a phenomenon in which the physical properties of polysaccharide particles change through hydration, swelling, and collapse processes when polysaccharides are heated with water or mixed with water and a base. More specifically, the micellar structure in the polysaccharide particles absorbs water molecules, causing the polysaccharide particles to swell, and then the micellar structure in the polysaccharide particles is collapsed by thermal energy or a base. In other words, in the preparation method, a hydroxide, which is a base that promotes gelatinization, is used with the polysaccharide, and a small amount of water is used compared to the polysaccharide, so that a rotating force is induced during the gelatinization process and thermal energy in the polysaccharide is continuously supplied, thereby further promoting gelatinization.
[0032] Therefore, in the above-mentioned manufacturing method, the polysaccharide capable of such gelatinization may not have reactive functional groups other than hydroxyl groups.For example, it is preferable that the polysaccharide is one or more selected from the group consisting of starch, dextrin, glycogen, inulin, cellulose, pectin, agar and guar gum.More preferably, the polysaccharide is starch or dextrin, which is a hydrolyzate thereof.
[0033] In particular, starch is preferred because it is contained in large amounts in foods such as potato, wheat, corn, rice, and tapioca, and is easily available. Such starch contains amylose and amylovectin, which may be contained in the starch in a weight ratio of 1:99 to 80:20. In terms of processability and solubility, it is advantageous for the amylovectin content to be equal to or greater than the amylose content. Such starch may be selected from potato starch, corn starch, rice starch, wheat starch, tapioca starch, and sweet potato starch, and potato starch, which has a high amylovectin content, may be more preferred.
[0034] In addition, the gelatinized polysaccharide produced in the above steps is not a fluid liquid dissolved or suspended in water, but a semi-solid gel. The gelatinized polysaccharide is mixed by the shearing action of the two screws and the chamber wall in the reactor, so that the torque and heat energy in the reactor can be maintained at a certain level or higher.
[0035] In order to maintain a torque value above a certain level after gelatinization of such polysaccharides, it is important to control the amount of water used. Therefore, in order to maintain the torque so that the carboxyalkylation reaction in the reactor proceeds smoothly while at the same time producing a carboxyalkylated polysaccharide having a uniform degree of substitution, water should be used in an amount of 0.35 to 1.0 times the weight of the polysaccharide.
[0036] On the other hand, when water is used in an amount less than 0.35 times the weight of the polysaccharide, the water evaporates due to the increased torque during the gelatinization process of the polysaccharide, which causes problems in workability and makes it difficult to produce a carboxyalkylated polysaccharide having a uniform degree of substitution. Also, when water is used in an amount more than 1.0 times the weight of the polysaccharide, the torque during the gelatinization process of the polysaccharide is reduced, which reduces the reaction efficiency and yield, and the cost of drying the water is increased, and the amount of by-products such as sodium chloride (NaCl) produced during the reaction process is increased, which may reduce the absorption performance of the superabsorbent polymer, which is undesirable.
[0037] More specifically, the water can be used in an amount of 0.35 times or more, 0.4 times or more, 0.45 times or more, 0.5 times or more, 0.6 times or more, or 0.7 times or more, and 1.0 times or less, 0.9 times or less, 0.8 times or less, 0.75 times or less, 0.74 times or less, 0.73 times or less, or 0.72 times or less, based on the weight of the polysaccharide.
[0038] Preferably, the water is used in an amount of 0.45 to 0.75 times the weight of the polysaccharide.
[0039] The water used may be ordinary water such as tap water, distilled water, deionized water, or purified water, without any restrictions, but preferably, distilled water can be used.
[0040] In addition, the hydroxide and metal salt of haloalkyl carboxylic acid are not dissolved in water before mixing with the polysaccharide, and the polysaccharide is not mixed with an organic solvent before mixing with the hydroxide, unlike the commonly known methods. Instead, in the method, all of the reactants for the carboxyalkylation reaction are charged into the reactor together with the solvent, which is expected to improve the production efficiency by shortening the production process.
[0041] In addition, when the polysaccharide is mixed with the hydroxide, the metal salt of the haloalkyl carboxylic acid, and water, no other solvent is used other than water. Examples of the other solvents that are commonly used other than water include alcoholic solvents such as ethanol, methanol, and isopropyl alcohol, and solvents that are miscible with water, such as acetone, 1,4-dioxane, dimethylformamide, and dimethyl sulfoxide.
[0042] If no water is used as a solvent for the gelatinization and carboxyalkylation of polysaccharides, the hydroxide and metal salt of haloalkyl carboxylic acid are difficult to mix with the polysaccharides, and the reaction does not proceed. If a solvent other than water is mixed with water, not only environmental problems and recovery costs may occur, but also safety problems may occur due to evaporation due to the low boiling point. In addition, if a solvent other than water is mixed with water in the reactor, it may harden and cause mixing problems because it prevents the gelatinization of the polysaccharides. However, in the above-mentioned production method, such problems can be overcome by using only water as a solvent in the gelatinization and carboxyalkylation of polysaccharides.
[0043] Meanwhile, the polysaccharide used in the preparation method includes an anhydroglucose unit (AGU) represented by the following chemical formula 1, and the molecular weight of the anhydroglucose unit (AGU) is 162.14. [ka]
[0044] In Formula 1, the numbering refers to the position of each carbon, and carboxyalkylation may occur at the hydroxyl group at the second carbon (C2), third carbon (C3), or sixth carbon (C6) in the anhydroglucose unit (AGU). For example, carboxymethylated polysaccharides are those in which one or more hydroxyl groups (OH) in the anhydroglucose unit (AGU) are substituted with a carboxymethyl group (OCH2COOH / OCH2COO - ) is substituted.
[0045] For example, when an alkali metal salt of a haloacetic acid is used as the metal salt of a haloalkyl carboxylic acid, the carboxyalkylated polysaccharide finally produced by the above-mentioned production method contains a carboxymethylated glucose unit represented by the following formula 2. [ka]
[0046] In the above Chemical Formula 2, R is independently hydrogen, CH2COO - M + or CH2COOH, However, at least one of R is CH2COO - M + or CH2COOH, where M represents an alkali metal.
[0047] The degree of substitution (DS) of the carboxyalkyl group in the carboxyalkylated polysaccharide produced by this production method may be 0.6 to 1.1. If the degree of substitution (DS) of the carboxyalkyl group is too low, it cannot be sufficiently dissolved in the dissolution process of water required for producing the superabsorbent resin, resulting in a problem of reduced water retention capacity of the superabsorbent resin. If the degree of substitution (DS) of the carboxyalkyl group is too high, the production of side reaction products increases, resulting in reduced reaction efficiency and biodegradability, which is undesirable.
[0048] More specifically, the degree of substitution (DS) of the carboxyalkyl group may be 0.6 or more, 0.62 or more, or 0.64 or more, and 1.1 or less, 1.05 or less, 1.0 or less, 0.96 or less, 0.9 or less, 0.8 or less, 0.7 or less, or 0.65 or less.
[0049] Here, the degree of substitution of the carboxyalkyl group (DS) refers to the average number of hydroxyl groups (-OH) substituted by the carboxyalkyl group per anhydroglucose repeating unit. In other words, since there are three hydroxyl groups per glucose repeating unit, the theoretical maximum degree of substitution is 3, and a degree of substitution of 0.1 means that three hydroxyl groups are substituted per 10 glucose repeating units. In addition, the degree of substitution of such acidic groups is determined by the average number of hydroxyl groups (-OH) substituted by the carboxyalkyl group per anhydroglucose repeating unit. 1 It can be calculated through 1 H NMR analysis.
[0050] In this case, the carboxyalkylated polysaccharide may be a carboxymethylated one, and therefore the degree of substitution (DS) of the carboxyalkyl group in the carboxyalkylated polysaccharide may be regarded as the degree of substitution of the carboxymethyl group in the carboxymethylated polysaccharide.
[0051] The hydroxide may be at least one selected from the group consisting of sodium hydroxide, potassium hydroxide, and lithium hydroxide, with sodium hydroxide (NaOH) being the most preferred in terms of availability.
[0052] The hydroxide can be used in an amount of 0.5 to 1.5 equivalents based on the number of moles obtained by dividing the weight (g) of the polysaccharide by the molecular weight of the anhydroglucose unit (AGU). Specifically, the equivalent amount of the hydroxide used can be calculated by dividing the weight (g) of the hydroxide used by the molecular weight to determine the number of moles, and then dividing the calculated number of moles of hydroxide by the number of moles of polysaccharide calculated by dividing the weight (g) of the polysaccharide used by 162.14, which is the molecular weight of the anhydroglucose unit (AGU).
[0053] More preferably, the hydroxide can be used in an equivalent amount of 0.5 to less than 1.2 based on the molar amount calculated by dividing the weight (g) of the polysaccharide by the molecular weight of anhydroglucose unit (AGU). If the equivalent amount of the hydroxide used is too low, the reaction may not proceed due to insufficient hydroxide, resulting in a low degree of carboxyalkyl substitution in the final carboxyalkylated polysaccharide. If the equivalent amount of the hydroxide used is too high, a process of neutralizing the high pH with unreacted hydroxide is required, which may result in the generation of by-products that reduce the absorption capacity.
[0054] More specifically, the hydroxide can be used in an amount of 0.5 or more, 0.6 or more, or 0.7 or more, and 1.15 or less, 1.1 or less, 1.0 or less, 0.9 or less, or 0.8 or less, based on the number of moles of the weight (g) of the polysaccharide divided by the molecular weight of anhydroglucose unit (AGU).
[0055] The metal salt of haloalkylcarboxylic acid means a metal salt of alkylcarboxylic acid (alkylcarboxylic acid, alkanoic acid, R-COOH, where R is alkyl) having at least one halogen substituent, in other words, a compound in which an anion of alkylcarboxylic acid having at least one halogen substituent and a metal cation are ionically bonded. Here, the metal salt may be an alkali metal salt, an alkaline earth metal salt, or a second transition metal salt. The halogen substituent may be preferably chloro or bromo. The alkyl group may be linear or branched, and the number of carbon atoms may be, but is not limited to, 1 to 20, or 1 to 10. Specific examples of the alkyl group include methyl, ethyl, propyl, n-propyl, isopropyl, butyl, n-butyl, isobutyl, tert-butyl, sec-butyl, 1-methylbutyl, 1-ethylbutyl, pentyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, 1-ethylpropyl, 1,1-dimethylpropyl, hexyl, n-hexyl, 1-methylpentyl, 2-methylpentyl, 4-methyl-2-pentyl, 3,3-dimethylbutyl, and 2-ethylbutyl. , heptyl, n-heptyl, isohexyl, 1-methylhexyl, 2-methylhexyl, 3-methylhexyl, 4-methylhexyl, 5-methylhexyl, cyclopentylmethyl, cyclohexylmethyl, octyl, n-octyl, tert-octyl, 1-methylheptyl, 2-ethylhexyl, 2,4,4-trimethyl-1-pentyl, 2,4,4-trimethyl-2-pentyl, 2-propylpentyl, n-nonyl, and 2,2-dimethylheptyl.
[0056] Such metal salts of haloalkyl carboxylic acids may be alkali metal salts of haloalkyl carboxylic acids.
[0057] In one embodiment, when the carboxyalkylated polysaccharide is carboxymethylated, the metal salt of the haloalkyl carboxylic acid may be an alkali metal salt of a haloacetic acid.
[0058] In further embodiments, the metal salt of a haloalkyl carboxylic acid may be an alkali metal salt of an alkyl carboxylic acid substituted with at least one chloro.
[0059] In still other embodiments, the metal salt of a haloalkyl carboxylic acid may be an alkali metal salt of at least one chloro-substituted acetic acid.
[0060] Preferably, in consideration of reactivity, the metal salt of the haloalkyl carboxylic acid may be an alkali metal salt of chloroacetic acid.
[0061] The alkali metal chloroacetate may be one or more selected from the group consisting of sodium monochloroacetate (SMCA), potassium monochloroacetate, and lithium monochloroacetate. Preferably, sodium monochloroacetate (SMCA) is used in consideration of availability and reactivity.
[0062] For example, when sodium monochloroacetate is used as the metal salt of the haloalkyl carboxylic acid, the final carboxymethylated polysaccharide contains a repeating unit represented by the following formula 2-1. [ka]
[0063] In the above formula 2-1, R1 is independently hydrogen, CH2COO - Na + or CH2COOH, However, at least one of R1 is CH2COO - Na + , or CH2COOH.
[0064] In this case, the metal salt of haloalkyl carboxylic acid can be used in an amount of 0.5 to 1.5 equivalents based on the number of moles obtained by dividing the weight (g) of the polysaccharide by the molecular weight of the anhydroglucose unit (AGU). Specifically, the equivalent amount of the metal salt of haloalkyl carboxylic acid used can be calculated by dividing the weight (g) of the metal salt of haloalkyl carboxylic acid used by the molecular weight to determine the number of moles, and then dividing the calculated number of moles of the metal salt of haloalkyl carboxylic acid by the number of moles of the polysaccharide obtained by dividing the weight (g) of the polysaccharide used by 162.14, which is the molecular weight of the anhydroglucose unit (AGU).
[0065] More preferably, the metal salt of haloalkyl carboxylic acid can be used in an equivalent amount of 0.5 to less than 1.2 based on the molar amount of the weight (g) of the polysaccharide divided by the molecular weight of anhydroglucose unit (AGU). If the content of the metal salt of haloalkyl carboxylic acid is too low, the hydroxyl group of the polysaccharide is not sufficiently substituted with carboxymethyl, and if the content of the metal salt of haloalkyl carboxylic acid is too high, chloroacetic acid or glycolic acid is formed as a by-product of a side reaction that occurs during the reaction, and the reaction efficiency of the carboxymethylated polysaccharide is reduced by neutralization with hydroxide. In addition, if the pH is reduced by the neutralization reaction, a crosslinking reaction may occur during the reaction, resulting in a reduction in absorption capacity.
[0066] More specifically, the metal salt of the haloalkyl carboxylic acid can be used in an equivalent amount of 0.5 or more, 0.6 or more, or 0.7 or more and 1.15 or less, 1.1 or less, 1.0 or less, 0.9 or less, or 0.8 or less based on the number of moles calculated by dividing the weight (g) of the polysaccharide by the molecular weight of anhydroglucose unit (AGU).
[0067] The metal salt of the haloalkyl carboxylic acid can be used in an amount of 1 to 1.29 moles per mole of the hydroxide. If the metal salt of the haloalkyl carboxylic acid is used in an amount that is too large or too small compared to the hydroxide, the substitution reaction of the carboxyalkyl group may not proceed sufficiently to achieve the degree of substitution (DS) of the carboxyalkyl group in the above range, and the content of sodium chloride (NaCl), which is a by-product that may be generated during the reaction, may increase. In addition, the overproduction of haloalkyl carboxylic acid or glycolic acid may cause a problem of partially forming a crosslinked structure. More specifically, the metal salt of the haloalkyl carboxylic acid and the hydroxide can be used in a molar ratio of 1:1.
[0068] Also, the mixing may be performed in a state where 70 to 95% of the total volume of the reactor is filled. If the total volume of the reactants filled in the reactor is too small, the torque may not increase enough to cause the carboxyalkylation reaction during gelatinization, and if the total volume of the reactants filled in the reactor is too large, there is a disadvantage that the carboxyalkylation substitution reaction does not occur uniformly due to the difficulty in feeding the reactants into the reactor.
[0069] More specifically, the mixing may be carried out in a state where the reactor is filled to 70% or more, 75% or more, 76% or more, or 77% or more of the total volume, and 95% or less, 94% or less, 93% or less, or 92% or less.
[0070] In addition, the reactor for producing the carboxyalkylated polysaccharide may be any kneading machine that is equipped with two screws or a rotor with blades and can induce torque and thermal energy. For example, an internal mixer such as a Banbury mixer or an Intermix mixer, or a two-roll mill may be used.
[0071] Preferably, an internal mixer can be used as the reactor.
[0072] The mixing may be performed for 5 to 15 minutes. At this time, the two screws or the bladed rotor installed in the reactor may rotate at 30 to 100 rpm. More preferably, the mixing may be performed for 10 minutes.
[0073] Here, the gelatinization of the polysaccharide may be completed within 2 / 5 of the total mixing time from the start of mixing. The completion of the gelatinization of the polysaccharide may be confirmed when the torque stabilizes when the internal torque in the reactor is measured from the start of mixing to the end of mixing using the temperature and torque measuring sensors installed in the reactor as described above. For example, when the total mixing time is 10 minutes, the gelatinization of the polysaccharide may be completed within 4 minutes.
[0074] Meanwhile, the temperature inside the reactor after gelatinization of the polysaccharide may be maintained at 90 to 110° C. This is because the internal heat energy increases due to the load induced during the gelatinization process, causing the internal temperature inside the reactor to increase until the completion of gelatinization, but after the completion of gelatinization, no additional load is induced, so the temperature is maintained within a certain range. Therefore, by maintaining not only the torque but also the temperature at a certain level or higher after gelatinization of the polysaccharide, the substitution efficiency of the carboxyalkyl group of the polysaccharide can be further improved.
[0075] More specifically, the temperature in the reactor after gelatinization of the polysaccharide may be 90°C or more, 92°C or more, 94°C or more, or 96°C or more, and 110°C or less, 105°C or less, 100°C or less, less than 100°C, 99°C or less, 98°C or less, or 97°C or less.
[0076] When the reactor is an internal mixer as described above, the temperature and torque in the reactor can be measured through temperature and torque measuring sensors between the two screws.
[0077] The method may further include a step of dissolving the product in water and then precipitating the resultant in an alcohol-based organic solvent, in order to purify the product, carboxyalkylated polysaccharide, and obtain a carboxyalkylated polysaccharide from which impurities have been removed.
[0078] Here, the alcohol-based organic solvent may be at least one selected from the group consisting of methanol, ethanol, and isopropyl alcohol.
[0079] The alcohol-based organic solvent can be used in an amount (ml / g) of 10 to 60 times the volume of the product produced, of which methanol is most preferred in terms of purification efficiency and cost.
[0080] In addition, the method may further include, after the above step, a step of recovering a precipitate by filtration under reduced pressure, and a step of drying the recovered precipitate, whereby a carboxyalkylated polysaccharide from which remaining hydroxides and generated by-products have been effectively removed can be obtained.
[0081] (Method of manufacturing biodegradable highly water-absorbent resin) The method for producing a biodegradable superabsorbent resin having improved water retention capacity includes the following steps.
[0082] Step 1: dissolving the carboxyalkylated polysaccharide produced by the above-mentioned production method in water in an amount of 5 to 15 times the weight of the carboxyalkylated polysaccharide; The product of step 1 is then subjected to self-crosslinking under a pH condition of 6 to 8 while being dried (step 2).
[0083] Step 1 First, in step 1, the carboxyalkylated polysaccharide prepared by the above-mentioned preparation method is dissolved in water in an amount of 5 to 15 times the weight of the carboxyalkylated polysaccharide, and through this step, self-crosslinking in the solution in step 2 described below occurs sufficiently.
[0084] Here, if the carboxyalkylated polysaccharide is dissolved in less than 5 times the weight of the polysaccharide in water, a precipitate will solidify, making it difficult to remove by-products. If the carboxyalkylated polysaccharide is dissolved in more than 15 times the weight of the polysaccharide in water, there may be a problem of increased costs due to excessive use of solvent.
[0085] The dissolution in step 1 may be carried out under normal temperature and pressure conditions, where normal temperature means a temperature of about 21 to about 23° C., and normal pressure means atmospheric pressure without any applied pressure.
[0086] Step 2 Step 2 is a step of drying the product of step 1 and crosslinking it under a condition of pH 6 to 8, and the pH can be adjusted using, for example, an aqueous hydrochloric acid solution, an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, etc., but is not limited thereto, and can be adjusted using an acid / base solution commonly used for adjusting pH. Through this step, a crosslinked polymer is produced in which polysaccharides are crosslinked with each other through an esterification reaction within the carboxyalkylated polysaccharides.
[0087] In particular, the crosslinking reaction in step 2 is a self-crosslinking reaction, and a crosslinking agent that is generally used in the preparation of crosslinked polymers of superabsorbent resins is not used. More specifically, meth(acrylate)-based compounds such as polyethylene glycol (meth)acrylate and ethylene glycol di(meth)acrylate, and epoxy-based compounds such as ethylene glycol diglycidyl ether, propylene glycol, and glycerin are generally used as crosslinking agents, but such crosslinking agents are not used in the preparation method. If a crosslinking agent were to be used, the content of biomass-based raw materials in the final superabsorbent resin would decrease, so it is advantageous to self-crosslink carboxyalkylated polysaccharides without a separate crosslinking agent in order to improve biodegradability.
[0088] In addition, a reaction catalyst and / or a heat stabilizer for accelerating the esterification reaction may be further used during the crosslinking reaction.
[0089] The esterification catalyst may be 4-dimethylaminopyridine (DMAP), magnesium acetate, tetra-n-butyl titanate (TBT), lead acetate, sodium acetate, potassium acetate, antimony trioxide, N-methylimidazole, or a combination thereof. The catalyst may be used in an amount of 0.1 to 5 moles per mole of the carboxyalkylated polysaccharide to shorten the reaction time and obtain a desired degree of crosslinking. Specifically, the reaction catalyst may be used in an amount of 0.1 moles or more, 0.5 moles or more, 1 mole or more, or 2 moles or more, and 4.5 moles or less, 4 moles or less, or 3.5 moles or less per mole of the carboxyalkylated polysaccharide.
[0090] In addition, an organic or inorganic phosphorus compound can be used as the heat stabilizer. The organic or inorganic phosphorus compound may be, for example, phosphoric acid, an organic ester of phosphoric acid, phosphorous acid, or an organic ester of phosphorous acid. More specifically, commercially available substances such as phosphoric acid, alkyl phosphates, or aryl phosphates can be used as the heat stabilizer.
[0091] In addition, during the crosslinking reaction, additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant may be further used, if necessary.
[0092] In addition, the self-crosslinking reaction in step 2 is carried out under a condition of pH 6 to 8. If the pH in the self-crosslinking reaction is less than 6, the crosslinking reaction may occur too quickly, which may result in a decrease in the water retention capacity of the superabsorbent resin, and if the pH in the self-crosslinking reaction is more than 8, the crosslinking may occur too slowly or may not occur at all, which is not suitable.
[0093] Also, the drying in step 2 may be performed at a temperature of 100 to 130° C. The drying method may be selected and used without any limitation as long as it is a commonly used method. Specifically, the drying step may be performed by a method such as hot air supply, infrared radiation, ultrashort wave radiation, or ultraviolet radiation.
[0094] Specifically, the drying may be performed under vacuum conditions, and the drying time may be about 30 minutes to about 4 hours, or about 2 to about 3 hours, taking into consideration process efficiency, etc.
[0095] In addition, the drying method can be selected and used without any limitation as long as it is a method usually used for producing a highly water-absorbent resin. Specifically, the drying step can be performed by a method such as hot air supply, infrared radiation, ultrashort wave radiation, or ultraviolet radiation. The water content of the crosslinked polymer produced after such drying may be about 5 to about 10% by weight.
[0096] Additional steps The method may further include, after step 2, a step of pulverizing and classifying the crosslinked polymer produced in step 2.
[0097] However, a coarse pulverization step may be selectively carried out prior to pulverization of the crosslinked polymer.
[0098] The coarse pulverization process is a process for increasing the drying efficiency in the subsequent drying process and controlling the particle size of the superabsorbent resin powder finally produced. The pulverizer used here is not limited in configuration, and specifically, any one may be selected from the group of pulverizing equipment consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a meat chopper, and a disc cutter.
[0099] In addition, the coarse pulverization process may be performed so that the crosslinked polymer has a weight average particle size of about 2 to about 10 mm, for example. It is technically difficult to pulverize the crosslinked polymer to a particle size of less than 2 mm due to the high moisture content of the crosslinked polymer, and the pulverized particles may aggregate with each other. On the other hand, if the crosslinked polymer is pulverized to a particle size of more than 10 mm, the efficiency of the subsequent drying step may be reduced.
[0100] A step of grinding and classifying the coarsely ground crosslinked polymer may then be performed.
[0101] The pulverization process may be carried out so that the particle size of the crosslinked polymer powder, i.e., the base resin, is about 150 to about 850 μm. Specific examples of the pulverizer used to pulverize to such a particle size include a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, and a jog mill, but the present invention is not limited to the above examples.
[0102] After the pulverization step, the pulverized crosslinked polymer powder may be classified according to particle size in order to control the physical properties of the final superabsorbent resin.
[0103] The resulting superabsorbent polymer may have a powder form with a particle size of 150 to 850 μm, which may be measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP 220.3 method.
[0104] In addition, the superabsorbent polymer may satisfy a centrifugation retention capacity (CRC) of 30 to 45 g / g as measured by the EDANA method WSP 241.3. More specifically, the centrifugation retention capacity (CRC) of the superabsorbent polymer may be 30 g / g or more, 35 g / g or more, 37 g / g or more, 39 g / g or more, 39.2 g / g or more, 40 g / g or more, 41 g / g or more, or 41.2 g / g or more, and 45 g / g or less, 44 g / g or less, or 43.5 g / g or less.
[0105] The present invention will be described in more detail with reference to the following examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited thereto. EXAMPLES
[0106] Example - Preparation of Carboxymethylated Starch Determination of Moisture Content of Potato Starch The moisture content of potato starch is the content of moisture relative to the total weight of the potato starch obtained, and can be calculated as a percentage by subtracting the weight of dried potato starch from the total weight of potato starch and dividing the result by the total weight of potato starch. Here, the weight of dried potato starch is calculated using a moisture analyzer to measure the weight when the weight change is within 0.001 g and no change occurs for 30 seconds or more when dried at 125°C. The moisture content of the potato starch used in the examples, comparative examples and reference examples was measured using the above method, and was found to be 17% by weight, which indicated that the actual starch content in the potato starch was 83% by weight.
[0107] Example 1-1 In an internal mixer reactor, 28 g of potato starch (manufactured by DAESANG, moisture content 17% by weight) (actual starch content taking moisture content into account: 23.24 g, 0.143 mol), 4.01 g of NaOH (0.1 mol, 0.7 equivalents relative to the number of moles of starch), 11.69 g of SMCA (0.1 mol, 0.7 equivalents relative to the number of moles of starch) and 12 g of distilled water were charged to 77% of the reactor volume, and mixed at 50 rpm for 10 minutes to carry out starch gelatinization and carboxymethylation reactions.
[0108] At this time, the internal torque and temperature in the reactor during mixing were measured using temperature and torque measuring sensors located between two screws installed in the internal mixer reactor. As a result of the measurement, it was confirmed that starch gelatinization was completed within 3 minutes from the start of mixing, and that the torque and temperature in the reactor were maintained at 7 to 9 Nm and 96.3±1° C., respectively, after starch gelatinization.
[0109] The produced carboxymethyl starch was collected, dissolved in distilled water, and precipitated in methanol in an amount (ml / g) 40 times the volume of the carboxymethyl starch, followed by filtration under reduced pressure and drying to obtain purified carboxymethylated starch.
[0110] Example 1-2 (Step 1) Into an internal mixer reactor, 33.4 g of potato starch (manufactured by DAESANG, moisture content 17% by weight) (actual starch content taking moisture content into consideration: 27.72 g, 0.171 mol), 4.79 g of NaOH (0.12 mol, 0.7 equivalents relative to the number of moles of starch), 13.94 g of SMCA (0.12 mol, 0.7 equivalents relative to the number of moles of starch) and 14.31 g of distilled water were charged to 92% of the reactor volume, and the mixture was mixed at 50 rpm for 10 minutes to carry out starch gelatinization and carboxymethylation reactions.
[0111] At this time, the internal torque and temperature in the reactor during mixing were measured using temperature and torque measuring sensors located between two screws installed in the internal mixer reactor, and the measured results are shown in a graph in Figure 1. As a result of the measurement, it was confirmed that starch gelatinization was completed within 3 minutes from the start of mixing, and that the torque and temperature in the reactor were maintained at 8 to 10 Nm and 96.4±1°C, respectively, after starch gelatinization.
[0112] Then, an additional purification step was carried out in the same manner as in Example 1-1 to obtain purified carboxymethylated starch.
[0113] Comparative Example 1-1 200L of isopropyl alcohol (IPA) was added to a flask, and 20g of potato starch (manufactured by DAESANG, moisture content 17% by weight) (actual starch content considering moisture content: 16.60g, starch content 0.102mol) and 4.34g of NaOH (0.109mol, 1.06 equivalents to the number of moles of starch) were dispersed therein, and the temperature was maintained at 70°C. Then, 20g of distilled water and 12.65g of SMCA (0.109mol, 1.06 equivalents to the number of moles of starch) were added and reacted for 5 hours to produce carboxymethylated starch. At this time, in the case of Comparative Example 1-1, starch gelatinization and carboxymethylation reactions were carried out in the flask together with an excess amount of solvent, so that torque in the flask was not sufficiently induced.
[0114] Next, an additional purification step was carried out in the same manner as in Example 1-1 to obtain purified carboxymethylated starch.
[0115] Comparative Example 1-2 400L of isopropyl alcohol (IPA) was added to the flask, and 200g of potato starch (manufactured by DAESANG, moisture content 17% by weight) (actual starch content considering moisture content: 166g, 1.02mol) and 30.71g of NaOH (0.768mol, 0.75 equivalents to the number of moles of starch) were dispersed therein, and the temperature was maintained at 70°C. Then, 77g of distilled water and 89.44g of SMCA (0.768mol, 0.75 equivalents to the number of moles of starch) were added and reacted for 5 hours to produce carboxymethylated starch. At this time, in the case of Comparative Example 1-2, the starch gelatinization and carboxymethylation reactions were carried out in the flask, so that the torque in the flask was not sufficiently induced.
[0116] Next, an additional purification step was carried out in the same manner as in Example 1-1 to obtain purified carboxymethylated starch.
[0117] Comparative Example 1-3 An internal mixer reactor was filled with 28 g of potato starch (manufactured by DAESANG, moisture content 17% by weight) (actual starch content taking moisture content into account: 23.24 g, 0.143 mol), 6.91 g of NaOH (0.173 mol, 1.2 equivalents relative to the number of moles of starch), 20.11 g of SMCA (0.173 mol, 1.2 equivalents relative to the number of moles of starch), 3 g of distilled water, and 9 g of IPA to a volume of 95% of the reactor, and mixed at 50 rpm for 10 minutes to carry out starch gelatinization and carboxymethylation reactions.
[0118] At this time, the internal torque and temperature inside the reactor during mixing were measured using temperature and torque measuring sensors located between two screws installed in the internal mixer reactor, and the measured results are shown in a graph in Figure 2. As a result of the measurement, it was confirmed that starch gelatinization was completed within 3 minutes from the start of mixing, and after starch gelatinization, the torque inside the reactor continued to rise to 90 Nm or more and the temperature to 130°C or more. As a result, the carboxymethylation reaction was difficult to carry out, and carboxymethylated starch with a uniform degree of substitution was not obtained.
[0119] Reference Example 1-1 An internal mixer reactor was filled with 28 g of potato starch (manufactured by DAESANG, moisture content 17% by weight) (actual starch content taking moisture content into account: 23.24 g, 0.143 mol), 6.91 g of NaOH (0.173 mol, 1.2 equivalents relative to the number of moles of starch), 20.11 g of SMCA (0.173 mol, 1.2 equivalents relative to the number of moles of starch) and 12 g of distilled water to a volume of 90% of the reactor, and mixed at 50 rpm for 10 minutes to carry out starch gelatinization and carboxymethylation reactions.
[0120] At this time, the internal torque and temperature inside the reactor during mixing were measured through temperature and torque measuring sensors located between two screws installed in the internal mixer reactor, and the measured results are shown in a graph in Figure 3. As a result of the measurement, it was confirmed that starch gelatinization was completed within 3 minutes from the start of mixing, and that the torque and temperature inside the reactor were maintained at 8 to 10 Nm and 96.9±1°C, respectively, after starch gelatinization.
[0121] Then, an additional purification step was carried out in the same manner as in Example 1-1 to obtain purified carboxymethylated starch.
[0122] Reference Example 1-2 An internal mixer reactor was filled with 28 g of potato starch (manufactured by DAESANG, moisture content 17% by weight) (actual starch content taking moisture content into account: 23.24 g, 0.143 mol), 6.91 g of NaOH (0.173 mol, 1.2 equivalents relative to the number of moles of starch), 20.11 g of SMCA (0.173 mol, 1.2 equivalents relative to the number of moles of starch), 6 g of distilled water, and 6 g of glycerol to a volume of 93% of the reactor, and mixed at 50 rpm for 10 minutes to carry out starch gelatinization and carboxymethylation reactions.
[0123] At this time, the internal torque and temperature inside the reactor during mixing were measured through temperature and torque measuring sensors located between two screws installed in the internal mixer reactor, and the measured results are shown in a graph in Figure 4. As a result of the measurement, it was confirmed that starch gelatinization was completed within 4 minutes from the start of mixing, and that the torque and temperature inside the reactor were maintained at 16 to 18 Nm and 102.5±1°C, respectively, after starch gelatinization.
[0124] Then, an additional purification step was carried out in the same manner as in Example 1-1 to obtain purified carboxymethylated starch.
[0125] Reference Example 1-3 An internal mixer reactor was filled with 28 g of potato starch (manufactured by DAESANG, moisture content 17% by weight) (actual starch content taking moisture content into account: 23.24 g, 0.143 mol), 6.91 g of NaOH (0.173 mol, 1.2 equivalents relative to the number of moles of starch), 20.11 g of SMCA (0.173 mol, 1.2 equivalents relative to the number of moles of starch), 6 g of distilled water, and 6 g of IPA to a volume of 88% of the reactor, and mixed at 50 rpm for 10 minutes to carry out starch gelatinization and carboxymethylation reactions.
[0126] At this time, the internal torque and temperature inside the reactor during mixing were measured through temperature and torque measuring sensors located between two screws installed in the internal mixer reactor, and the measured results are shown in a graph in Figure 5. As a result of the measurement, it was confirmed that starch gelatinization was completed within 4 minutes from the start of mixing, and that the torque and temperature inside the reactor were maintained at 12 to 15 Nm and 98.4±1°C, respectively, after starch gelatinization.
[0127] Then, an additional purification step was carried out in the same manner as in Example 1-1 to obtain purified carboxymethylated starch.
[0128] The starch content in the potato starch, the moisture content in the potato starch, the total water content added, the amounts of water and additional solvents used relative to the weight of starch, and the equivalent amounts of NaOH and SMCA used in the above-mentioned Examples, Comparative Examples, and Reference Examples are summarized in Table 1 below.
[0129] Example - Production of superabsorbent polymer Example 2-1 (Step 1) The carboxymethylated starch produced in Example 1-1 was dissolved in water in an amount 10 times by weight relative to the weight of the carboxymethylated starch.
[0130] (Step 2) Thereafter, the product of step 1, which has a pH of 7.5 to 8, was adjusted to pH 6.5 using 3% hydrochloric acid aqueous solution, and dried and self-crosslinked for 2 to 3 hours while supplying hot air at 120°C in an oven with a variable airflow direction to produce a crosslinked polymer under the above pH.
[0131] (Additional Step) Then, the crosslinked polymer was pulverized in a pulverizer and classified to select particles having a size of 150 to 850 μm, which was used as the final product, the highly water-absorbent resin.
[0132] Example 2-2, Comparative Example 2-1, Comparative Example 2-2, and Reference Examples 2-1 to 2-3 Superabsorbent resins were prepared in the same manner as in Example 2-1, except that the carboxymethylated starches prepared in Example 1-2, Comparative Example 1-1, Comparative Example 1-2, and Reference Examples 1-1 to 1-3 were used instead of the carboxymethylated starch prepared in Example 1-1.
[0133] Test Example 1: Measurement of the degree of substitution of carboxymethylated starch (1) Measurement of the actual degree of substitution First, each of the carboxymethylated starches prepared in the above Examples, Comparative Examples and Reference Examples was 1 Prepare samples for H NMR analysis 1 H NMR spectra were obtained. 1 For the H NMR analysis, carboxymethylated starch dissolved in H20 was added to MeOH, stirred, filtered, and dried to prepare 50 mg of sample. The prepared sample was dissolved in 0.75 mL of D20 and 0.25 mL of D2SO4, which are NMR measurement solvents, and stirred at 90 °C for 1 hour. It was confirmed that the sample turned deep yellow.
[0134] Thereafter, the carboxymethylated starches produced in Examples 1-1, 1-2, Reference Examples 1-1, 1-2 and 1-3 are shown in Figures 6 to 10, respectively. 1 The H NMR spectrum was shown.
[0135] More specifically, the degree of substitution of the carboxymethylated starch prepared in Example 1-1 was measured as follows.
[0136] 1) Carboxymethylated starch produced in Example 1-1 1 After obtaining the H NMR spectrum, the sum of the integrals of the peaks within 2.5-3.6 ppm, namely 2.57 ppm, 2.58 ppm, 2.60 ppm, 2.64 ppm, 2.66 ppm, 3.15 ppm, 3.16 ppm, 3.33 ppm, and 3.34 ppm, were set to 1.
[0137] 2) Next, the degree of substitution at the second carbon (2-DS) was calculated as the sum of the integrals at the peaks at 3.34 ppm, 3.33 ppm (doublet, 0.23) and 2.57 ppm, 2.58 ppm (doublet, 0.20), the degree of substitution at the third carbon (3-DS) was calculated by dividing the integral values at the peaks at 2.39 ppm and 2.41 ppm (0.20) by 2, and the degree of substitution at the sixth carbon (6-DS) was calculated by dividing the integral values at the peaks at 2.14 ppm and 2.15 ppm (0.19) by 2.
[0138] 3) The degree of substitution at the second carbon (2-DS), the degree of substitution at the third carbon (3-DS), and the degree of substitution at the sixth carbon (6-DS) were then summed to determine the degree of substitution (DS) of the carboxylmethyl group.
[0139] In the same manner, the degree of substitution of the carboxymethyl group of the carboxymethylated starch produced in the other Examples, Comparative Examples and Reference Examples was determined, and the degree of substitution was substantially 1Since some shift in the 1 H NMR spectrum may occur, the results of the measurement of the degree of substitution compared with the spectrum of Example 1-1 are shown in Table 2.
[0140] (2) Calculation of reaction efficiency (RE, %) The reaction efficiency (RE, %) was calculated according to the following formula 1, and the results are shown in Table 2. [Formula 1] Reaction efficiency (RE,%) = [(actual degree of substitution) / (expected degree of substitution)] × 100 In the above formula 1, The expected degree of substitution refers to the dosage equivalent of SMCA added per mole of starch.
[0141] Test Example 2: Measurement of Centrifuge Retention Capacity (CRC) of Superabsorbent Resin The water retention capacity of the superabsorbent resins produced in the Examples, Comparative Examples, and Reference Examples was measured in terms of the absorbency under no load according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP 241.3, and the results are shown in Table 3.
[0142] Specifically, the superabsorbent resins prepared in the Examples, Comparative Examples, and Reference Examples were classified using a sieve of #30-50 to obtain only superabsorbent resins having particle sizes of 300 to 600 μm. Such superabsorbent resins W0(g) (approximately 0.17 g) were evenly placed in a nonwoven fabric envelope, sealed, and then immersed in physiological saline (0.9 wt%) at room temperature. After 30 minutes, the envelope was dewatered for 3 minutes at 250 G using a centrifuge, and the mass W2(g) of the envelope was measured.
[0143] Moreover, the same procedure was carried out without using the resin, and the mass W1 (g) was then measured. Using the obtained masses, the CRC (g / g) was calculated according to the following formula 2. [Formula 2] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1
[0144] [Table 1]
[0145] [Table 2]
[0146] [Table 3]
[0147] Referring to Tables 1 to 3, it can be seen that the production methods of the Examples in which starch gelatinization and carboxymethylation are carried out using a specific content of water and a specific level of torque is maintained after starch gelatinization show significantly improved reaction efficiency compared to the production method of Comparative Example 1-1 in which starch gelatinization and carboxymethylation are carried out using an excess amount of solvent according to a commonly known production method.
[0148] In addition, in the case of the carboxymethylated starch prepared in Comparative Example 1-2, the degree of substitution is similar to that of the Examples, using an equivalent amount of SMCA, but the water retention capacity of the final superabsorbent polymer is significantly lower than that of the superabsorbent polymer prepared using the carboxymethylated starch of the Examples. This is believed to be because, unlike the Examples, the torque is not sufficiently induced in the flask reactor, and the torque cannot be maintained at a constant level after starch gelatinization, and therefore the carboxymethyl groups cannot be uniformly substituted for the carboxymethylated starch of the Examples.
[0149] In addition, it was confirmed from Comparative Examples 1-3 that if an excessively low water content is used during the gelatinization and carboxymethylation reactions of starch, the internal torque of the reactor continues to increase after gelatinization, making it impossible to produce a uniformly substituted carboxymethylated starch.
[0150] In addition, it can be seen from Reference Examples 1-1 to 1-3 that the efficiency of the carboxymethylation reaction can be improved by adjusting the equivalent amount of the reactants to an appropriate amount and using water as the sole solvent for carboxymethylation.
Claims
1. The method includes mixing a polysaccharide, a hydroxide, a metal salt of a haloalkyl carboxylic acid, and water in a reactor to carry out a gelatinization and carboxyalkylation reaction of the polysaccharide; The water is used in an amount of 0.35 to 1.0 times the weight of the polysaccharide, The torque in the reactor is maintained at 7 to 18 Nm after gelatinization of the polysaccharide; Method for producing carboxyalkylated polysaccharides.
2. The process according to claim 1, wherein no other solvent is used other than water.
3. The method according to claim 1, wherein the water is used in an amount of 0.45 to 0.75 times the weight of the polysaccharide.
4. The method according to claim 1 , wherein the polysaccharide is at least one selected from the group consisting of starch, dextrin, glycogen, cellulose, pectin, inulin, agar and guar gum.
5. 2. The process according to claim 1, wherein the degree of substitution (DS) of the carboxyalkyl groups in the produced carboxyalkylated polysaccharide is from 0.6 to 1.
1.
6. The method of claim 1 , wherein the carboxyalkylated polysaccharide is carboxymethylated.
7. The method according to claim 1 , wherein the mixing is carried out in a state where the reactor is filled to 70 to 95% of its total volume.
8. The method according to claim 1, wherein an internal mixer is used as the reactor.
9. The method according to claim 1 , wherein the hydroxide is at least one selected from the group consisting of sodium hydroxide, potassium hydroxide, and lithium hydroxide.
10. The method according to claim 1, wherein the hydroxide is used in an amount of 0.5 to less than 1.2 equivalents based on the number of moles obtained by dividing the weight (g) of the polysaccharide by the molecular weight of an anhydroglucose unit (AGU).
11. The method according to claim 1 , wherein the metal salt of a haloalkyl carboxylic acid is an alkali metal salt of chloroacetic acid.
12. The method according to claim 11, wherein the alkali metal chloroacetate is at least one selected from the group consisting of sodium monochloroacetate (SMCA), potassium monochloroacetate, and lithium monochloroacetate.
13. The method according to claim 1 , wherein the metal salt of the haloalkyl carboxylic acid is used in an amount of 1 to 1.29 moles per mole of the hydroxide.
14. The method of claim 1 , wherein the mixing is carried out for 5 to 15 minutes.
15. The method according to claim 1 , wherein the gelatinization of the polysaccharide is completed within ⅔ of the total mixing time from the start of mixing.
16. The method according to claim 1, wherein the temperature in the reactor is maintained at 90 to 110°C after gelatinization of the polysaccharide.
17. The method according to claim 1, further comprising the step of dissolving the produced product in water and then precipitating it in an alcohol-based organic solvent.
18. The method according to claim 17, wherein the alcohol-based organic solvent is at least one selected from the group consisting of methanol, ethanol, and isopropyl alcohol.
19. Step 1: dissolving the carboxyalkylated polysaccharide produced by any one of the methods according to claims 1 to 18 in water in an amount of 5 to 15 times the weight of the carboxyalkylated polysaccharide; Step 2: subjecting the product of step 1 to self-crosslinking while drying under a pH condition of 6 to 8; A method for producing a biodegradable highly water-absorbent resin.
20. The method according to claim 19, wherein the produced superabsorbent polymer satisfies a centrifuge retention capacity (CRC) of 30 to 45 g / g as measured by EDANA method WSP 241.
3.
21. The method according to claim 19, wherein the dissolving in step 1 is carried out under normal temperature and pressure conditions.
22. The method of claim 19, wherein the drying in step 2 is carried out at a temperature of 100 to 130° C.
23. The method according to claim 19, further comprising the steps of pulverizing and classifying the crosslinked polymer produced in step 2 after step 2.
Citation Information
Patent Citations
Production of carboxymethyl ether salt of sweet potato starch pulp
JP1991146502A
Production of carboxymethyl ether salt of corn starch pulp
JP1991146503A
Method for producing carboxymethylcellulose
JP2010106197A
Method for producing carboxymethyl cellulose
JP2012036375A
Carboxyalkyl starch particles permeated with acidic gas, extruded material, and process for producing it.
JP2012518711A